The Yezidis : the History of a Community, Culture and Religion. - Açıkyıldız, Birgül (Library of modern religion ;, 2010)
Yezidism is a fascinating part of the rich cultural mosaic of the Middle East. Yezidis emerged for the first time in the 12th century in the Kurdish mountains of northern Iraq. Their religion, which has become notorious for its associations with 'devil worship', is in fact an intricate syncretic system of belief, incorporating elements from proto-Indo-European religions, early Persian faiths like Zoroastrianism and Manichaeism, Sufism and regional paganism like Mithraism. Birgul Acikyildiz offers a comprehensive appraisal of Yezidi religion, society and culture. Written without presupposing an.